Wetland Biodiversity of Telaga Air, Sarawak: Perception and Conservation of Local - M. Dayang Affizzah, A; Salbiah, E; Athirah, B; Shuib, M (International Journal of Engineering and Technology, 2018)
Wetland are among the most productive of the world’s ecosystem and the most threatened tropical ecosystem. Mangrove forest is very useful and gives various benefits and it is extremely productive ecosystem that provide numerous good and services both to the marine environment and people. This research was conducted to identify the factors that influence the perception of local communities towards wetland biodiversity conservation which brings more beneficial towards our daily life. The interest group for this study is focuses on communities who live near the mangroves forest area and the location of study is in Telaga Air, Sarawak. The method that been used in this study was Factor Analysis and multiple regression. There are 15 factors that have been extracted by using Factor Analysis. Out of the factors, only 7 factors that are chosen as independent variables to run the regression analysis with the dependent variable of respondent’s Perception. Lastly, the study found that the factors of community awareness, garbage disposal and level of pollution have a strong relationship with the perception of residents towards wetland biodiversity conservation in Telaga Air. Overall, this study shows that majority of local communities that live nearby mangroves shows a positive attitude towards the conservation of wetland in Kuching. All the activities that being carried out in mangrove area should be monitor by authorities in order to ensure the sustainable of the mangrove forest are protected and guaranteed.